Shear resistance of steel fibre reinforced concrete beams - Pal, Shilpa; Kumar, Abhishek; Arif, Mohammed; Shariq, M. (Journal of Structural Engineering, 2024)
The purpose of the present research is to investigate the shear behavior of fibre reinforced concrete beams under fourpoint loading condition. Three types of fibres were examined: hooked-end steel fibre, crimped-steel fibre and continuousdeformed-steel fibres. The experimental program consists of cubes to test the compressive strength of concrete, cylindersto test the tensile strength of concrete and beams to test the shear and flexure strength of concrete. Simply supportedRC beams 150×150 mm cross section and 700 mm length were used in this study. The reinforcement was provided inthree ways viz. conventional minimum steel reinforcement at top and bottom with stirrups in accordance with theprovisions of IS 456, conventional minimum bottom steel reinforcement without stirrups incorporating crimped steelfibre in 03%, 0.4% and 0.5% dose and crimped steel fibre in 1.5% dose without top and bottom steel reinforcementand stirrups. The shear span to depth ratio was varied as 0.5, 1, 1.25 and 1.5. The experimental program consistedof twenty sets of beam specimens giving a total of forty beams in two replications each. The aim of this research is toinvestigate the effectiveness of fibres on the shear strength and ultimate load carrying capacities.